Transforming growth factor type beta induces monocyte chemotaxis and growth factor production. - Wahl, S M (1987)
Recent studies have focused on the potential role of transforming growth factor type beta (TGF-beta) as an immunoregulatory peptide. In this context, we demonstrate that TGF-beta is a potent chemoattractant for human peripheral blood monocytes. At concentrations from 0.1 to 10 pg/ml, TGF-beta induces directed monocyte migration in vitro. Consistent with this observation is the expression of high-affinity TGF-beta receptors on the monocytes with a Kd of 1-10 pM. At higher concentrations of TGF-beta (greater than or equal to 1 ng/ml), monocytes are stimulated to generate biologically active mediator(s) that enhance fibroblast growth. Gene expression for one of these growth factors, interleukin 1, is induced in monocytes within hours after exposure to TGF-beta. Thus, TGF-beta may provide an important signal for monocyte recruitment and for regulation of their synthesis of mediators of fibroblast growth and activity in wound healing.